A new laser device for ultra-rapid and sustainable aerosol sterilization. (June 2022) - Vuerich, Roman; Martinelli, Valentina; Vodret, Simone; Bertani, Iris; Carletti, Tea; Zentilin, Lorena; Venturi, Vittorio; Marcello, Alessandro; Zacchigna, Serena
Graphical abstract: The current COVID-19 pandemic has highlighted the relevance of aerosol-based infections. This work describes a laser device able to rapidly sterilize aerosol containing infectious viruses and bacteria, including Legionella pneumophila and SARS-CoV-2, when aerosolized by a novel system able to mimic droplet formation during human speech. This is a major advantage over existing devices that either purify incoming air through filters or sterilize solid surfaces, which are not major transmission routes. Abstract: The current COVID-19 pandemic has highlighted the importance of aerosol-based transmission of human pathogens; this therefore calls for novel medical devices which are able to sterilize contaminated aerosols. Here we describe a new laser device able to sterilize droplets containing either viruses or bacteria. Using engineered viral particles, we determined the 10, 600 nm wavelength as the most efficient and exploitable laser source to be manufactured in a commercial device. Given the lack of existing working models to reproduce a human aerosol containing living microbial particles, we developed a new system mimicking human droplet formation and preserving bacterial and viral viability. This evidenced the efficacy of 10, 600 nm laser light to kill two aerosol transmitted human pathogens, Legionella pneumophila and SARS-CoV-2. The minimal exposure time of <15 ms was required for the inactivation of over 99% pathogens in the aerosol; this is a key element in the design of a device that is safe and can be used in preventing inter-individual transmission. This represents a major advantage over existing devices, which mainly aim at either purifying incoming air by filters or sterilizing solid surfaces, which are not the major transmission routes for airborne communicable diseases.